Uprooting dynamics of a model tree under rockfall impact: Combined experimental and numerical insights - Zhang, Chenyang; Yu, Chenghao; Leung, Anthony Kwan; Mohammad, Sadeghi; Choi, Clarence Edward (Earth surface processes and landforms, 2025)
Climate change already increases the number of rockfalls or flow‐like landslides, posing a significant threat to human lives and public infrastructure in mountainous regions. Characterizing the dynamic uprooting response during rockfall‐tree interaction is essential for understanding the protective capabilities of forests in mitigating these hazards. In this study, a novel model tree is developed to evaluate the uprooting resistance against instantaneous impact. A lamina emergent torsional (LET) joint is introduced to simulate the root‐soil plate rotation behaviour. Then, a large‐scale pendulum experiment is used to validate the statical and dynamic uprooting responses of the model tree. A numerical model is used to back‐analyse the experiments and subsequently, a parametric study is performed. Our results demonstrate that the model tree closely reproduces the static and dynamic uprooting behaviours of natural trees, providing an accessible tool for further physical model experiments on rockfall and landslide impacts. The dynamic uprooting response of a tree is governed by both impact force and contact duration. Under instantaneous impacts, three distinct response regimes are observed: quasi‐static, impulse and intermediate. In most impact scenarios, trees exhibit responses in the impulse and intermediate regimes, indicating that static‐based criteria are insufficient for assessing uprooting stability. Consequently, we propose a dynamic failure criterion for predicting tree uprooting during rockfall interactions based on an empirical relationship between the critical impact duration and the normalized maximum impact turning moment. This criterion enables the prediction of dynamic tree uprooting failure using rockfall velocities, rockfall masses and stem diameters. We developed a dynamic failure criterion to predict tree uprooting failure during rockfall‐tree interactions, based on laboratory tests and numerical modelling. For a given rockfall impact situation, dynamic tree uprooting failure can be predicted based on rockfall velocities, rockfall masses and stem diameters.